POTENSI PERTUMBUHAN TRUBUSAN PADA TUNGGAK SISA PENEBANGAN POHON Eucalyptus pellita - Fanny, Rudang; Sulaeman, Rudianda; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Forest is a natural resource which has an usefull existency to life. Development on plantation of industrial forest (HTI) needs to choose a kind of suitable plant which Eucalyptus pellita is the one that can be easily adapted. Stumps of Eucalyptus pellita from residual logging in the head office of University of Riau area produces coppices which can be a source of vegetative multiplication of plant. The aim of this research is to perceive a potential of the third generation of coppices which are able to grow in one stump of Eucalyptus pellita residual logging and to perceive the growth of the third generation of coppices on the stump of residual logging. This research exercises using an observation method. This specimen taken exercises a purpossive sampling method. The result of this observation indicates that coppices which grow on the stump of Eucalyptus pellita residual logging have a potential in avarage amount of 9 coppices in each stump so that can be produced aprroximately 14.400 coppices/ha in a grow distance 2.5m x 2.5 m. This third generation has an average amount of 60 pieces of leaves in each stump and 10,5 cm high average accretion in 8 day measurement. Keywords:Eucalyptus pellita, Coppice, Growth.